Effects of fatigue and different crimp sizes on muscle synergies during dead hangs: a pilot study on climbers - Exel, J.; Kaufmann, P.; Platzer, L.; Kraner, M.; Gáspari, A.; Baca, A.; Kainz, H. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aim of this pilot study was to investigate the impact of different hold sizes on the motor control of upper body muscles during intermittent dead hangs. Four elite-level climbers (3 females, 1 male, 25.5 ± 6.8 years, 166.0 ± 7.8 cm height, 59.0 ± 8.8 kg weight, and 21.0 ± 1.4 IRCRA scale climbing grade ability) performed body-weight intermittent isometric dead hangs (7:3 s work-to-relief ratio) until failure, using a half-crimp position, onto edges of 10- and 30-mm. Muscle activations of upper limb muscles were recorded with surface electromyography electrodes and then used to calculate muscle synergies and forces were measured on an instrumented hang board. Results showed that two synergies were mainly used during the intermittent test: Synergy 1 with a higher contribution of the hand muscles, and Synergy 2 with higher contributions of the arm and trunk muscles. A cross-correlation analysis showed high correlations of both synergies between each crimp size (Synergy 1 and 2 at 10 and 30 mm had r = 0.98 and r = 0.89, respectively). A detailed correlation analysis throughout the whole time series indicated close to fatigue, Synergy 1 decreases activation while Synergy 2 increases, especially in the second half of the dead hang cycle. Our findings provide a nuanced understanding of upper body muscle involvement in intermittent dead hangs, informing future research on motor control and fatigue in climbing-related activities.